Retrograde intrarenal surgery in the prone split-leg position for female upper urinary tract stones: a preliminary study of 16 cases - Cao, Yu; Li, Mingshi; Cao, Wanbin; Tang, Li; Chen, Shenglan (Frontiers in Surgery, 2025)
ObjectivesThis study aims to preliminarily investigate the potential technical advantages of the prone split-leg position for treating upper urinary tract stones and evaluate its efficacy using computed tomography (CT).Materials and methodsA retrospective analysis was conducted on the clinical data of 16 female patients who underwent retrograde intrarenal surgery (fURS) for upper urinary tract stones in the prone split-leg position at our hospital between July and September 2024. All patients were treated using flexible ureteroscopes and received CT scans before and after the operation to assess surgical outcomes.ResultsAll surgeries were successfully performed in the prone split-leg position, with an average operation time of 62.25 ± 25.92 min. The immediate stone clearance rate was 100%, and no complications were observed.ConclusionRetrograde intrarenal surgery in the prone split-leg position is an effective treatment for upper urinary tract stones in female patients. This position facilitates ureteroscopic access to the renal pelvis and the insertion of ureteral guide sheaths, improves the immediate stone clearance rate, reduces intrarenal pressure, and represents an efficient, economical, and safe treatment method.